Business Strategy Development for Health-Tech SaaS Startups: A Case Study of Assist.id - Muhammad Fachruddin; Harimukti Wandebori (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The rapid digital transformation of Indonesia’s healthcare sector has created both vast opportunities and intense competition for health-tech Software-as-a-Service (SaaS) providers. Assist.id, a popular Indonesian health-tech SaaS startup with over 6,000 client clinics, experienced early growth but reached a strategic inflection point requiring a formal strategy. This study analyzes Assist.id’s strategic gaps and develops a business-level strategy to ensure sustainable competitive advantage. Using a qualitative case study approach, data were collected via in-depth interviews with company executives and clients, and analyzed through frameworks including Segmentation-Targeting-Positioning (STP), external environmental analysis, value chain and VRIN analysis, and SWOT/TOWS. The findings reveal that Assist.id’s core issue is an inefficient internal feedback loop leading to a feature gap, which, combined with regulatory changes, exposes the firm to freemium-priced competitors in the low-end segment and feature-rich rivals in the high-end segment. To address this, an integrated cost leadership and differentiation strategy is proposed. Key initiatives include launching a compliant freemium tier to defend the volume-driven segment, accelerating R&D for advanced features to strengthen the value-driven segment, and aligning organizational processes to rapidly respond to market feedback. The case offers broader insights for early-stage SaaS startups in health-tech on balancing cost and differentiation to achieve sustainable competitive advantage in a dynamic, regulated market.